Cancer survivors exercise at higher intensity in outdoor settings: The GECCOS trial. Issue 5 (23rd December 2020) - Miller, Jonathan M.; Sadak, Karim T.; Shahriar, Arman A.; Wilson, Natalie J.; Hampton, Maree; Bhattacharya, Manami; Towle, Ali; Turcotte, Lucie M.
Abstract: Purpose: : This randomized cross‐over group pilot trial assessed feasibility of recruiting survivors from a long‐term follow‐up clinic to an exercise group and measured whether outdoor or indoor exercise sessions better supported exercise motivation and behaviors in survivors of cancer. Methods: : Sixteen adolescent and young adult survivors of any cancer completed indoor and outdoor exercise sessions in this randomized cross‐over pilot trial. Measures of physical activity, motivation, and fatigue were taken 2 weeks before and 2 weeks after indoor sessions and 2 weeks before and 2 weeks after outdoor sessions. Measures of physical activity and fatigue were also taken during each exercise session. Results: : Initial recruiting of 19 participants met recruiting goals. Survivors who attended the most sessions lived an average of 8.7 km closer to the clinic. Objectively measured physical activity intensity was 0.63 metabolic equivalents of a task (METs) per minute greater during outdoor exercise sessions as compared to indoor exercise sessions. There were no meaningful differences in long term, habitual physical activity behavior, motivation, or fatigue in the weeks following the outdoor exercise sessions as compared to the indoor exercise sessions. Conclusions: : This study shows the feasibility of recruiting survivors from a long‐term follow‐up clinic to community‐based exercise groups. Although this brief pilot intervention did not show significant effects on habitual physical activity behavior or motivation in adolescent and young adult survivors of cancer, the greater exercise intensity during the outdoor exercise sessions indicate that holding group exercise sessions for survivors outdoors may promote greater intensity during exercise.